Preventive and Curative Efforts in Archive Management Planning for the Threat of Natural Disasters in Indonesia - Erliyana, Ella; Rozanti, Dwi Wahyu (Record and Library Journal, 2019)
Background of the study: Archives have a very crucial role in the development of organization and institutions, Including in Indonesia. The importance of archival protection is in Determine records management planning in overcoming the impact of natural disasters.Purpose: The Efforts taken are preventive and curative actions that aim to minimize the risk of losing archives and as an effort to safeguard the importance of policy-making towards archives in the future.Method: This research is qualitative research with literature study method. The researcher raised a study that was in accordance with the topic of understanding, then made a map of the data related to preventive and curative Efforts in an effort to overcome natural disasters. In this case, the analysis of data is done through reference to books, journals, and other library materials Articles regarding preventive and curative actions in archival management and policy planning related to archives. Literature studies pay attention to relevance to the subject matter and to facilitate the understanding and direction of writing in accordance with the problems in the study.Findings: The results of this study indicate that disaster management consists of stages several items, namely mitigation, preparedness, response, and recovery.Conclusion: Prevailing Efforts are focused more on Preventing and protecting conventional archives from the disaster damage. The actions taken include storing archives in a safe and disaster-resistant place, storing archives with special equipment (vaulting), duplicating or duplicating records by transferring media in the form of Microfilms, microfiche, magnetic recordings, electronic records. While curative Efforts are repairs or maintenance of records with conditions that have or have begun to be damaged. Actions include lamination, encapsulation, reproduction of archives and recovery.